On the Issue of the Educational and Upbringing Components of Continuing Economic Education - M. G. Sergeyeva; N. L. Sokolova; I. S. Samokhin (Научный диалог)
The educational and upbringing components of continuing education (economic education and economic upbringing) are considered. The relevance of the chosen topic is determined by the stable correlation between the continuity of school and vocational education and its effectiveness. It is noted that within the framework of the new educational paradigm conditions are being created that allow the future employee to constantly raise his own qualification taking into account the transforming requirements to the content and methods of his activity. A review of the theoretical literature on the phenomenon of continuing education and its specifics in the contemporary (primarily Russian) context is given. The study of the factors that have an impact on the educational and upbringing process allows authors to view economic education as an important component of “global human education”. The principles of the author's concept of continuous economic education, which emphasizes the role of the upbringing component of the educational process, are stated. The main stages of economic education are accentuated, with emphasis on the education of the individual, its key tasks, as well as the forecasted advantages for Russian schools and professional educational institutions (Higher Education Institutions and Secondary Specialized Educational Institutions) are defined. The authors come to the conclusion that in the foreseeable future, continuing economic education should be transformed into a system for stimulating the constant self-improvement of the individual in an unstable social economic context.